Use of Generative Artificial Intelligence to Create Sustainable Supply Chain Management: An Online Retail Perspective - Thakre, Bharat (ExcelingTech, 2025)
Generative artificial intelligence (AI) refers to the type of AI that is capable of creating such new contents as music, images, texts, videos, and codes, using expansive AI models, known as foundation models, that will help to learn from and simulate large volumes of data. Modern e-commerce businesses have realized that application of such sophisticated technology in supply chain management (SCM) to create efficient and sustainable supply chains. This article explains how Generative AI can be useful in this respect especially in a world where SCM is undergoing significant transformations due to changing consumer behavior and the changing nature of trade and commerce in an internet driven world.